Evidence of Clostridium perfringens epsilon toxin associated with multiple sclerosis. (April 2019) - Wagley, Sariqa; Bokori-Brown, Monika; Morcrette, Helen; Malaspina, Andrea; D'Arcy, Caroline; Gnanapavan, Sharmilee; Lewis, Nicholas; Popoff, Michel R; Raciborska, Dominika; Nicholas, Richard; Turner, Ben; Titball, Richard W
Background: It was recently reported that, using Western blotting, some multiple sclerosis (MS) patients in the United States had antibodies against epsilon toxin (Etx) from Clostridium perfringens, suggesting that the toxin may play a role in the disease. Objective: We investigated for serum antibodies against Etx in UK patients with clinically definite multiple sclerosis (CDMS) or presenting with clinically isolated syndrome (CIS) or optic neuritis (ON) and in age- and gender-matched controls. Methods: We tested sera from CDMS, CIS or ON patients or controls by Western blotting. We also tested CDMS sera for reactivity with linear overlapping peptides spanning the amino acid sequence (Pepscan) of Etx. Results: Using Western blotting, 24% of sera in the combined CDMS, CIS and ON groups ( n  = 125) reacted with Etx. In the control group ( n  = 125), 10% of the samples reacted. Using Pepscan, 33% of sera tested reacted with at least one peptide, whereas in the control group only 16% of sera reacted. Out of 61 samples, 21 (43%) were positive to one or other testing methodology. Three samples were positive by Western blotting and Pepscan. Conclusion: Our results broadly support the previous findings and the role of Etx in the aetiology of MS warrants further investigation.